SUCCESSES AND FAILURES OF AICPA INITIATIVES: IMPACT OF DIVERSITY DECLINE ON MINORITIES - Elizabeth Foma (Journal of Economics, Business, and Accountancy Ventura, 2013)
This is a qualitative research examining the impact of diversity in the Certified Public Accounting(CPA) profession and the successes and failures of the American Institute of Certified PublicAccountants (AICPA) initiatives to address this issue. It also examined current state of diversity inthe CPA profession and found that while the actual head count of minorities in the professionincreased, the percentage of representation dropped. The success of the initiative has been theability to convince schools to seek more diversity in recruitment. The AICPA initiatives failedbecause of lack of financial resources available to minorities to continue their education as well aslack of awareness. The research suggests ways of encouraging minority interest in the CPAprofession. Beside, this research examined the benefits of the initiatives, current AICPA goals aswell as future challenges. Despite the several initiatives proposals and implementations to attractminorities into the CPA profession, minority representation is still at its lowest. However, the futurelooks bright because minority owned firms are increasing even though there is a decreasingenrollment of minority accounting students in colleges. As the number of CPA firms increases,mentorship programs can be developed to help increase minority interest in the accountingprofession.